2020
DOI: 10.3390/app10082972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chloride Resistance of Early-Strength Concrete Using Blended Binder and Polycarboxylate-Based Chemical Admixture

Abstract: The mixing proportions of concrete were examined with regard to the durability performance and early strength in coastal areas. Research was conducted to improve the C24 mix (characteristic strength of 24 MPa). C35 concrete (characteristic strength of 35 MPa) was selected as a comparison group, as it exhibits the minimum proposed strength criterion for concrete in the marine environment. To secure the early strength of the C24 concrete, 50% of the total ordinary Portland cement (OPC) binder was replaced with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As per Fig. 1 , the bio-engineered CaCO 3 is nano-scaled in size, and hence has a finer particles size as compared to the Ordinary Portland Cement (OPC) particles (which is in the range of 10μm in average) 95 . This fine aspect would likely improve the particle packing of concrete and give a superior spacer effect.…”
Section: Randd Translations: Potential Technological Applicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…As per Fig. 1 , the bio-engineered CaCO 3 is nano-scaled in size, and hence has a finer particles size as compared to the Ordinary Portland Cement (OPC) particles (which is in the range of 10μm in average) 95 . This fine aspect would likely improve the particle packing of concrete and give a superior spacer effect.…”
Section: Randd Translations: Potential Technological Applicationsmentioning
confidence: 93%
“…From cost effectiveness viewpoint, CaCO 3 can be used as a filler in Portland cement, reducing the product’s high cost. It was evidenced that replacement of cement by just 2% CaCO 3 helps reduce the CO 2 emission from cement plants by 69%, meeting the economic and environmental aspects of fly ash as well as contributing equal positive effects to concrete 93 95 .…”
Section: Randd Translations: Potential Technological Applicationsmentioning
confidence: 99%
“…Tang and Utgenannt [5] have suggested that the corrosion at the spacer locations may be due to the highly porous structure within the spacer itself. The supplementary cementitious materials (e.g., GGBS and fly ash) and polycarboxylate-based admixture were considered in the mix of concrete and spacer to improve their microstructures, as several studies [24] showed that these materials had a positive influence on the chloride resistance of concrete. * G5-20 aggregate was used for the chloride-resistant HPC(C).…”
Section: Design Of Concrete and Spacersmentioning
confidence: 99%
“…FA does not have the ability to bind particles or aggregates like cement, but with the fines size and presences of water in mix design, then SiO2 contained in FA will react chemically with Ca(OH)2 which formed by hydration process of cement and produces a substance that has bind ability. [5] Due to characteristics of both materials, many research by scientists had been developed and found many benefit of those material for substitute or partial replacement of cement such environmental friendly (due to reusing a waste material), increasing resistance to sulphate / chloride [6]- [10], reducing bleed rates [11], increasing compressive strength [2], [8], [12]- [15], increasing durability [8], [13], [16], and reducing permeability of concrete [8].…”
Section: Introductionmentioning
confidence: 99%